A biomechanical comparison of polymethylmethacrylate-reinforced and expansive pedicle screws in pedicle-screw revisions - Bostan, Bora; Esenkaya, Irfan; Gunes, Taner; Erdem, Mehmet; Asci, Murat; Kelestemur, M. Halidun; Sen, Cengiz (Turkish Assoc Orthopaedics Traumatology, 2009)
Objectives: Different techniques and choices exist for revision of pedicle screws, two of which are pedicle screw combined with cement augmentation and expansive pedicle screw fixation. This biomechanical study was designed to compare the pullout strengths of two different revision techniques. Methods: Fourteen lumbar vertebrae obtained from four calves (mean age 15 months) were divided into two groups equal in number. Monoaxial 6.0-mm pedicle screws were inserted into the right pedicles, and axial pullout testing was performed at a rate of 10 mm/min and failure strengths were recorded. Revision was performed with the same-sized pedicle screws reinforced with polymethylmethacrylate in group 1, and with 7.0-mm expansive pedicle screws in group 2, and pullout testing was repeated to record maximum revision pullout strengths. Results: The mean pullout strengths recorded before and after revision were significantly different in both groups, being 2,162.9 +/- 718.5 N and 2,794.3 +/- 979.2 N in group 1 (p=0.041) and 2,605.0 +/- 487.6 N and 3,327.1 +/- 640.8 N in group 2 (p=0.012), respectively. However, the mean pullout strengths recorded before and after revision did not differ significantly between the two groups (p>0.05). Conclusion: Our results showed that expansive pedicle screws 1 mm larger in diameter provide similar pullout strengths to those of same-sized, polymethylmethacrylate-reinforced screws in revision of pedicle screw fixation, suggesting that they can be preferred with the additional advantages of ease of application and avoiding risks for pedicle fracture and cement leakage.
Pedikül vida revizyonlarinda polimetilmetakrilat ile güçlendirilmiş ve ucu genişleyebilen pedikül vidalarinin biyomekanik karşilaştirilmasi
Keywords: Biomechanics; bone screws; cattle; lumbar vertebrae/surgery; spinal fusion/instrumentation; spine/surgery